Narcissism and helplessness: Some considerations about interpersonal relationships today - Barbosa, Caroline Garpelli [UNESP]; Campos, Erico Bruno Viana [UNESP]; Neme, Carmen Maria Bueno [UNESP] (FapUNIFESP (SciELO), 2021)
This essay aims to discuss the phenomenon of narcissism today, starting from the hypothesis that interpersonal relationships are configured by helplessness in its traumatic dimension, and not as an opening to alterity. This would be so because, in the current social scenario, human relationships tend to lack help and alteritarian support for subjects’ transformation and development, posing three disruptive threats to them: lonely emptiness, invasion of the other and impotence. In the absence of supportive relationships, the other appears as a threat against which narcissism emerges as a possibility of defense, prevailing in the form of regenerating narcissism.
Narcisismo y desamparo: Algunas consideraciones sobre las relaciones interpersonales en la actualidad
Narcissisme et détresse: Quelques considérations sur les relations interpersonnelles aujourd’hui
Keywords: desamparo; détresse; helplessness; interpersonal relationships; narcisismo; narcissism; narcissisme; psicanálise; psicoanálisis; psychanalyse; psychoanalysis; relaciones interpersonales; relations interpersonnelles; relações interpessoais